The Development of Learning Achievement in The Development of Southeast Asia of Mathayomsuksa 1 Students by Using Cooperative Learning Management Using STAD Technique - กอศรีพร กุลยา (Education journal Faculty of Education, Nakhon Sawan Rajabhat University, 2022)
The purposes of this research were to 1) To compare the of learning achievement of mathayomsuksa 1 students before and after receiving cooperative learning through STAD technique and 2) To compare the learning achievement of mathayomsuksa 1 students who received cooperative learning management using STAD technique with 60% criterion. The sample group consisted of mathayomsuksa 1 students at 1/1 of Thetsaban Wat Woranat Banphot school Mueang Nakhon Sawan district Nakhon Sawan province under Nakhon Sawan municipality, region 1, term 2, academic year 2019, amount 30 people, were obtained by simple random sampling using the classroom as a random unit. The tools used in this research consisted of 1) learning management plan with a collaborative model with STAD technique 2) Achievement test before and after learning. Data analysis were mean, standard deviation and t-test. The results were as follows: 1) Mathayomsuksa 1 students receiving cooperative learning management using STAD technique have higher academic achievement after studying statistical significance at the level of .05. and 2) Mathayomsuksa 1 students receiving cooperative learning management using STAD technique have academic achievement above the threshold of 60 percent with statistical significance at the level of .05.